Arbitration as the Dispute Settlement Method to Address Harmful Interference in the Age of Mega-Constellations of Satellites - Pratidina, Safira; Latipulhayat, Atip; Handayani, Irawati (International Law Department, Faculty of Law Universitas Padjadjaran, 2024)
The increasing demand for radio frequency spectrum usage for the launch of mega-constellations of telecommunication satellites will potentially increase incidents of harmful interference to radiocommunication. International law has yet to regulate a compulsory method of dispute settlement for harmful interference disputes. Currently, most cases of harmful interference are solved through technical and political means. However, those methods cannot address damage claims that may be caused by harmful interference, which may become increasingly common with the growing participation of private entities. Article 56 of the ITU Constitution has regulated several dispute resolution methods related to telecommunications, namely negotiation, diplomatic channels, other methods mutually agreed upon by the parties, and arbitration. This study aims to analyze these methods of dispute settlement and determine the most appropriate method to address harmful interference disputes. As the diplomatic dispute settlement methods do not result in enforceable legally binding decisions, this study argues that arbitration is the most appropriate method to settle disputes concerning harmful interference because it offers more neutrality in its proceedings and the confidentiality of sensitive information. It may also decide on damages as part of the arbitral award. Arbitration awards are final and binding, thus offering legal certainty to the parties to the dispute. States have generally recognized arbitration awards and created mechanisms to enforce arbitral awards. This study also recommends that the ITU implement compulsory arbitration with limitations and create a harm-claim threshold.